Castles landscape in the southeast of the Iberian Peninsula: the example of Castalla Castle between the 11th and 15th centuries - Antonio, Juan; Rico, Mira (Zakład Architektury Krajobrazu, Wydział Biologiczno-Rolniczy, Uniwersytet Rzeszowski, 2018)
Castalla Castle (Alicante, Spain), built between the 11th and 16th centuries, is one of the most outstanding fortifications in the province of Alicante, as part of al-Andalus, first, and the Kingdom of Valencia, after. The present work aims to deepen the knowledge of its landscape on a medium scale for a large part of the Middle Ages. In this way, analysing some material (archaeological) and cultural (written) sources, it has been possible to better draw the Castalla Castle landscape in the Foia de Castalla district, a geographic territory located in the north of the province of Alicante, between the 11th and 15th centuries and during two different chronocultural periods: Andalusian (11th century – 1244) and Christian (1244-1499).
Keywords: Andalusian landscape; Castalla Castle; feudal landscape; Foia de Castalla district; province of Alicante